Pt‐Functionalized Nanoporous TiO2 Nanoparticles With Enhanced Gas Sensing Performances Toward Acetone. Issue 14 (7th June 2018) - Xing, Xinxin; Chen, Nan; Yang, Yue; Zhao, Rongjun; Wang, Zhezhe; Wang, Zidong; Zou, Tong; Wang, Yude
Abstract : A facile hydrothermal method is used to prepare Pt‐functionalized nanoporous TiO2 nanoparticles. These are used as gas‐sensing material in sensors, fabricated according to the indirect heating method. Gas‐sensing performance of the sensors is investigated by testing their gas response to acetone, which exhibits favorable selectivity, good gas response value, fast response/recovery time, low detection concentration and good long‐term stability to acetone. Gas response β was defined as the ratio of Ra /Rg, where Ra and Rg are the resistance values of gas sensor exposed in air and objective gas, respectively. Among all these as‐prepared gas sensors, the 0.5% Pt‐functionalized TiO2 based gas sensor shows the highest gas response value of 29.51–200 ppm acetone at 300 °C, and the gas response value is 5.2 times higher than that (5.67) of pure TiO2 based gas sensor. It also has excellent selectivity to acetone when comparing with toluene, n‐butanol, isopropanol, ethanol, and methanol. The large specific surface area (168.101 m 2 g −1 ) provides enough contacting interface between gas and the as‐prepared materials, then the gas molecules could be broken into CO2 and H2 O by the active adsorbed oxygen species. The present results of the Pt‐functionalized TiO2 based gas sensors illustrates their potential application in detecting acetone. Abstract : A nanoporous 0.5%Pt‐functionalized TiO2 sample shows enhanced ability to capture more oxygen molecules and provides more active reaction sites on the interface to benefit the reaction between gas molecules and material. It exhibits excellent gas‐sensing performances, like high response value, fast response/recovery time, good repeatability, and reproducibility toward acetone gas.